BMAL1 controls the diurnal rhythm and set point for electrical seizure threshold in mice - Gerstner, Jason R.; Smith, George G.; Lenz, Olivia; Perron, Isaac J.; Buono, Russell J.; Ferraro, Thomas N. (Frontiers in Systems Neuroscience, 2014)
The epilepsies are a heterogeneous group of neurological diseases defined by the occurrence of unprovoked seizures which, in many cases, are correlated with diurnal rhythms. In order to gain insight into the biological mechanisms controlling this phenomenon, we characterized time-of-day effects on electrical seizure threshold in mice. Male C57BL/6J wild-type mice were maintained on a 14h/10h light/dark cycle, from birth until 6 weeks of age for seizure testing. Seizure thresholds were measured using a step-wise paradigm involving a single daily electrical stimulus. Results showed that the current required to elicit both generalized and maximal seizures was significantly higher in mice tested during the dark phase of the diurnal cycle compared to mice tested during the light phase. This rhythm was absent in BMAL1 knockout (KO) mice. BMAL1 KO also exhibited significantly reduced seizure thresholds at all times tested, compared to C57BL/6J mice. Results document a significant influence of time-of-day on electrical seizure threshold in mice and suggest that this effect is under the control of genes that are known to regulate circadian behaviors. Furthermore, low seizure thresholds in BMAL1 KO mice suggest that BMAL1 itself is directly involved in controlling neuronal excitability.